From gas to stars over cosmic time - Mac Low, Mordecai-Mark (Science, 2013)
Structured Abstract - Background Immediately after the Big Bang, the universe was uniform, homogeneous, and completely free of stars. The gravitational collapse of dark matter gathered gas with it that cooled, collapsed further, and formed stars. Observations over the past 20 years have revealed the dynamic star-formation history of the universe. The star-formation rate peaked 10 billion years ago, when stars formed an order of magnitude faster than in the modern universe. Deep observations have begun to reveal the early history of star formation, but how quickly star formation started remains controversial, with results from observations of early galaxies suggesting a slower start than distributions of distant gamma-ray bursts that trace young stars. However, simulations using standard prescriptions for energetic feedback from star formation (from stellar explosions and ionizing radiation) have tended to predict a substantially earlier peak than either of these methods shows. - The peak of star formation. Some 10 billion years ago, stars formed in the universe at a rate more than 20 times higher than the modern era. Star-forming galaxies light up the sky, whereas fainter filaments trace the distribution of dark matter that draws the gas together gravitationally in this numerical model. Understanding the history of star formation over cosmic time remains a major theoretical and observational challenge. [Credit: American Museum of Natural History/National Astronomical Observatory of Japan] - Advances Energetic feedback drives turbulence in diffuse gas that both promotes and inhibits star formation, with inhibition dominating over promotion, so that star formation does not efficiently trigger further star formation. Insufficient numerical resolution in simulations causes unphysical radiative cooling to occur in multiple ways, reducing the effectiveness of feedback in driving turbulence. Other mechanisms—such as magnetorotational instability, radiative heating, or accretion from the intergalactic medium—must also contribute to the observed gas velocity dispersions. Radiation pressure appears likely to be only modestly effective because of Rayleigh-Taylor instability in gas accelerated by it. Observed correlations between gas surface density and star-formation rate surface density can be reproduced by models including gravitational instability. Molecule formation may occur as a result of gravitational collapse rather than initiating it. Thus, gravitational instability seems to determine star formation, with the level of turbulence setting the critical density for instability. - Outlook Determining the early history of star formation will require the efforts of the largest ground and space-based telescopes under construction, such as the James Webb Space Telescope, the European Extremely Large Telescope, and the Large Synoptic Survey Telescope. Progress in models requires both better algorithms and larger computers. Adaptive meshes, both structured and unstructured, will play a critical role, as will hybrid algorithms that can take full advantage of the shared memory nodes of massively parallel computer clusters. A clear picture of star formation will underpin our understanding of the evolution of galaxies, including our own Milky Way, and of the history of the production and distribution of the elements heavier than helium, including those necessary for planet formation and for life. - Understanding Star Formation - Understanding how galaxies and the chemical composition of the universe evolved through cosmic time relies on unraveling the history of star formation over the universe's almost 14-billion-year history. Mac Low (p. 1229229) reviews the conditions of star formation in galaxies, focusing on the smaller-scale physics determining the conversion of gas into stars. Progress in understanding and modeling these processes and in observing galaxies at ever-earlier times are expected to lead to a convergence between model predictions and observations and to a full understanding of the cosmic history of star formation. - From the time the first stars formed over 13 billion years ago to the present, star formation has had an unexpectedly dynamic history. At first, the star-formation rate density increased dramatically, reaching a peak 10 billion years ago of more than 10 times the present-day value. Observations of the initial rise in star formation remain difficult, poorly constraining it. Theoretical modeling has trouble predicting this history because of the difficulty in following the feedback of energy from stellar radiation and supernova explosions into the gas from which further stars form. Observations from the ground and space with the next generation of instruments should reveal the full history of star formation in the universe, and simulations appear poised to accurately predict the observed history. - The author reviews the conditions of star formation in galaxies. - The author reviews the conditions of star formation in galaxies.
Gesehen am 10.06.2021